Enhancing the Shelf Life of Kunapajala and Shasyagavya and their Effects on Crop Yield - Ali, Md. N.; Chakraborty, S.; Paramanik, A. (International Journal of Bio-resource and Stress Management, 2023)
Organic farming is required for replenishing soil fertility and maintaining environmental sustainability. This exploratory study used two Vedic bio-inoculums Shasyagavya (3 different grades) and Kunapajala (4 different grades) to spray on black gram and mustard for evaluating the beneficial effects of bio-inoculums on crop yield and improving their shelf life. In black gram, Shasyagavya @ 20 and 10% spray and Kunapajala @ 5 and 10% spray produced better yields whereas highest yield was recorded with Shasyagavya 20% (0.11 kg m-2). In mustard, the only yield indicator which significantly varied among the treatments was 1000 seed weight. The average 1,000 seed weight was maximum (2.56 g) with Shasyagavya 10% spray and minimum (1.5 g) in control. Notably, Kunapajala 3% spray exhibited better result for most of the characters as compared to other treatments in mustard. Among the two carriers studied, charcoal performed better than glycerol. Further, it can be concluded that carrier based preparations could be stored for at least three months without compromising quality.